2001
DOI: 10.1152/jn.2001.85.2.605
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Synergies Encoded Within the Spinal Cord: Evidence From Focal Intraspinal NMDA Iontophoresis in the Frog

Abstract: This paper relates to the problem of the existence of muscle synergies, that is whether the CNS command to muscles is simplified by controlling their activity in subgroups or synergies, rather than individually. We approach this problem with two methods that have been recently introduced: intraspinal N-methyl-D-aspartate (NMDA) microstimulation and a synergy-extracting algorithm. To search for a common set of synergies encoded for by the spinal cord whose combinations would account for a large range of electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
189
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(203 citation statements)
references
References 31 publications
13
189
1
Order By: Relevance
“…Tresch found that the two sets of EMG responses were very similar to one another. In addition, the synergies evoked by NMDA were found by (Saltiel et al 2001) to be qualitatively similar to those described by Tresch.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Tresch found that the two sets of EMG responses were very similar to one another. In addition, the synergies evoked by NMDA were found by (Saltiel et al 2001) to be qualitatively similar to those described by Tresch.…”
Section: Introductionsupporting
confidence: 83%
“…Neither can it result from activating the fibers of passage of the descending fibers and those of the sensory systems. On the basis of these results, (Giszter et al, 1993 andSaltiel et al 2001) we have concluded that distinct interneuronal networks of the spinal cord must be the source of specific types of CFFs..…”
Section: Introductionmentioning
confidence: 79%
“…Both lines of research follow the general idea that a smaller number of variables (M-modes in our study or "synergies" in most other studies) can be used to construct behaviors with different characteristics (Loeb et al 2000;Saltiel et al 2001;d'Avella and Bizzi 2005;Ting and Macpherson 2005). A recent comparison of different methods to identify such M-modes ("synergies") has suggested that the results are robust across a variety of methods including principal component analysis and independent component analysis (Tresch et al 2006).…”
Section: Modes As Elemental Variablesmentioning
confidence: 55%
“…At the lower level, muscles form groups, within which their levels of activation co-vary across a wide range of tasks. Such groups have been referred to as muscle modes (M-modes, Krishnamoorthy et al 2003a,b) or muscle synergies (Ivanenko et al 2004(Ivanenko et al , 2005(Ivanenko et al , 2006Ting and Macpherson 2005;Torres-Oviedo and Ting 2007;Saltiel et al 2001;D'Avela et al 2005). At the upper level, the M-modes are considered as the elemental variables, and their co-variation is organized in a task-specific manner to stabilize an important performance variable.…”
Section: Introductionmentioning
confidence: 99%